AZAS FILOSOFIS PANCASILA SEBAGAI IDEOLOGI DAN DASAR NEGARA - Widisuseno, Iriyanto (HUMANIKA, 2014)
Pancasila state ideology and basic ontological value systems is a manifestation of people's lives Indonesian nation as the truth, be a way of life since the beginning of the history of the birth of the nation, so that they can survive up to now as a unifying and country basis. Epistemologically formation of ideology and the basic state through the political process and national spirit of our founding fathers. In axiologis, Pancasila state ideology and basic occupies imperative function as the norm and the direction of the destination society, nation and state.